Muamalah Fiqh Review of the Use of Contracts in Sharia Insurance Institutions - Muhamad Said; Mohammad Ghozali (al-Afkar, Journal For Islamic Studies, 2025)
Sharia economic growth in Indonesia has developed quite a bit in recent years. This was followed by growth in terms of financial institutions, both from the banking and non-bank sides. It can be seen from the contracts that are increasingly innovating like the multi-contracts that are now popular. Until one of the tabarru’ contracts which has the meaning of helping in sharia insurance institutions now feels like a tijaroh contract which spices up profits (profits) on transactions. The aim of this research is to examine the tabarru’ contract carried out by sharia insurance institutions by criticizing it through the tabarru’ theory approach itself from the perspective of muamalah fiqh. With qualitative research methods, sourced by secondary data, researchers try to describe the content of data collection techniques using deductive documentation methods. And found that insurance institutions still felt that capitalism was labeled sharia, and also concluded that zakat, infaq, shodaqoh and waqf (ZISWAF) institutions could be the best solution for Muslims to actually help them.